Becoming an Employer of Choice for Generation Z in the Construction Industry - Makram Bou Hatoum; Hala Nassereddine (Buildings)
The construction industry faces significant challenges including a critical skill shortage and an aging workforce, threatening the industry’s productivity, resilience, and knowledge retention. To address this issue, it becomes critical to attract, hire, and retain younger generations, particularly Generation Z (Gen Z), who are projected to become a dominant workforce by 2030. To this end, this study explores the employer preferences of Gen Z students joining the USA construction industry, providing valuable insights into their priorities and expectations. The study evaluates 27 employer of choice (EOC) factors to identify key criteria influencing Gen Z’s choice of employers. Analyses were conducted across various demographic and experiential categories, including gender, racial/ethnic backgrounds, first-generation status, those with loans, family influence, prior industry experience, intimidation by macho culture, and shifts in perspectives due to the COVID-19 pandemic. The findings reveal that Gen Z prioritizes respect, work–life balance, and job security, and values flexibility in work schedules and hybrid work environments. The findings were also used to propose eight recommendations for employers to become EOCs. Insights from this research serve a dual purpose by offering a foundation for further academic exploration and equipping industry practitioners with the data needed to tailor their recruitment and retention strategies to Gen Z.